Tibia Growth and Development in Broiler Chicks Reared under Continuous Light and Melatonin Dietary Supplementation During the First Two Weeks of Life - Vitorović Duško; Božičković Ivana; Lukić Miloš; Relić Renata; Škrbić Zdenka; Petričević Veselin; Lazarević Macanović Mirjana; Krstić Nikola (Acta Veterinaria, 2023)
The first few weeks after broilers hatch are the period of most intense bone growth and development, and the time when they are most susceptible to the influence of various external and internal factors. Research in the recent decades has focused on the involvement of melatonin in bone development during early life in chickens. Melatonin release from the pineal gland has a circadian rhythm, with the highest levels circulating during the night and decreasing during the light phase of the day. Various types of lighting are used in intensive broiler production. In this study, the effects of melatonin on the tibial structure and growth of broilers were investigated. During the first two weeks of life, two groups of chickens were kept under continuous light and fed the same diet, with the experimental group receiving melatonin in the amount of 0.03 g/kg of feed. The results obtained showed that the addition of melatonin in the diet had positive effects on the development and growth of the tibia, which was expressed in a significantly greater thickness of the diaphysis and cortical bone of the diaphysis, higher breaking force and higher values of alkaline phosphatase activity. The cortical bone mineral density of the tibia did not differ significantly between the groups of chicken.